Implication of High Body Fat Percentage on Migraine Chronification in Premenopausal Females - Pooja Ojha; Varun Malhotra (Neurology Research International)
Background. Chronic migraine, being a debilitating headache disorder, needs assessment of the risk factors implicated in its occurrence. We investigated the potential role of obesity as a risk for chronic migraine in premenopausal females with episodic migraine. Methods. In this analytical study, body fat% was compared between episodic and chronic migraine patient groups. The standard criteria of the international classification of headache disorder were used for the diagnosis. Demographic data, clinical details of migraine, and anthropometric measurements were collected using structured questions and standardized techniques. Pearson’s correlation (r) was estimated to assess the concordance between body fat% and migraine frequency. High body fat%’s implication on chronic migraine which was adjusted for body mass index (BMI), and the use of oral contraceptives was determined using logistic regression analysis. Results. A total of 168 premenopausal female migraineurs, with a mean (Standard deviation) age of 33.0 (±9.0) years, were enrolled in the study. BMI and high body fat% were significantly associated with chronic migraine (p<0.05). There was a weak positive, but significant, correlation between body fat% and migraine frequency (r = 0.185, p<0.017). The presence of high body fat was found to increase the risk of chronic migraine by 2.8 times (confidence interval 1.4–5.6; p<0.003). Conclusion. The amount of fat mass in the body relates to the clinical characteristics of migraine. There is an increased risk of developing chronic migraine in patients having high body fat. Weight control measures can be targeted for the prevention of migraine worsening.